The Changing Image of Zeus in Olympia - Barringer, Judith (Archäologischer Anzeiger, 2017)
Images of Zeus Keraunios dominate the visual representations of Zeus at Olympia throughout the archaic period and down to the 470s B.C., and this is especially true for military victory monuments erected in the Altis. In the 470s B.C., however, such images cease to appear, and military votives thereafter employ a serene and regal standing or seated image of the god. The change can be explained by a new role for Zeus and Olympia in the aftermath of the Persian Wars: as arbitrator of disputes between Greek poleis, as evidenced by a previously published inscription ca. 476–472 B.C. In accordance with this development, Zeus now acts as arbitrator in his visual manifestations at Olympia.